Descriptive analysis of bacon smoked with Brazilian woods from reforestation: methodological aspects, statistical analysis, and study of sensory characteristics - Saldaña E. (2018)
The authors are grateful to the São Paulo Research Foundation (FAPESP, Brazil) for funding the project No 2016/15012-2, and Cienciactiva for the Erick Saldaña PhD scholarship, from the “Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica (CONCYTEC, Peru; Contract 104-2016-FONDECYT).